Utilization of N-Hexane Extract of Turmeric (Curcuma longa) as an Acid-Base Titration Indicator - Sarmila; Sri Yolandari; Hasty Hamzah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Curcuma longa (turmeric) is a medicinal plant belonging to the Zingiberaceae family and is widely distributed in tropical regions. Turmeric contains various bioactive secondary metabolites, including curcumin, essential oils, and flavonoids. Curcumin, the principal pigment responsible for turmeric’s characteristic yellow color, exhibits pH-sensitive properties due to its amphoteric nature. This characteristic enables turmeric extract to respond to acidic and alkaline environments, indicating its potential application as a natural acid–base indicator. Objectives: This study aims to evaluate the effectiveness of turmeric extract as a natural indicator in acid–base titration and to compare its performance with standard synthetic indicators. Methods: An experimental approach was employed using the titration method. The titration process was conducted on three types of solution systems: (1) strong acid strong base, (2) weak acid strong base, and (3) strong acid weak base. Turmeric extract was used as the natural indicator. For comparison, two conventional synthetic indicators phenolphthalein and methyl orange were also applied. Observations focused on color changes and the corresponding pH values at the endpoint of each titration. Results: The findings demonstrated distinct color changes of turmeric extract in different solution systems. In the strong acid strong base titration, the color changed to orange-yellow at pH 8.06. In the strong acid weak base system, a pale yellow color was observed at pH 2.59. Meanwhile, in the weak acid strong base system, the solution exhibited a color transition from colorless to pink at pH 7.58. These results indicate that turmeric extract is responsive to pH variations and capable of signaling endpoint detection in titration processes. Conclusion: Turmeric extract shows potential as a natural acid–base indicator due to the pH-sensitive properties of curcumin. The observed color changes across different titration systems confirm its effectiveness in detecting acidic and alkaline conditions. Therefore, turmeric extract may serve as an alternative, environmentally friendly indicator in acid–base titration. Keywords: Turmeric extract; Curcumin; Natural indicator; Acid–base titration; pH sensitivity